Clinical and molecular epidemiology of veterinary blastomycosis in Wisconsin - Anderson, Jennifer L (BioMed Central, 2013)
BACKGROUND: Several studies have shown that Blastomyces dermatitidis, the etiologic agent of blastomycosis, is a genetically diverse pathogen. Blastomycosis is a significant health issue in humans and other mammals. Veterinary and human isolates matched with epidemiological case data from the same geographic area and time period were used to determine: (i) if differences in genetic diversity and structure exist between clinical veterinary and human isolates of B. dermatitidis and (ii) if comparable epidemiologic features differ among veterinary and human blastomycosis cases. RESULTS: Genetic typing of 301 clinical B. dermatitidis isolates produced 196 haplotypes (59 unique to veterinary isolates, 134 unique to human isolates, and 3 shared between canine and human isolates). Private allelic richness was higher in veterinary (median 2.27) compared to human isolates (median 1.14) (p = 0.005). Concordant with previous studies, two distinct genetic groups were identified among all isolates. Genetic group assignment was different between human and veterinary isolates (p < 0.001), with more veterinary isolates assigned to Group 2. The mean age of dogs diagnosed with blastomycosis was 6 years. Thirty cases were in male dogs (52%) and 24 were females (41%). The breed of dog was able to be retrieved in 38 of 58 cases with 19 (50%) being sporting breeds. Three of four felines infected with blastomycosis were domestic shorthair males between ages 6–12, and presented with disseminated disease. The other was a lynx with pulmonary disease. The equine isolate was from an 11-year-old male Halflinger with disseminated disease. Disseminated disease was reported more often in veterinary (62%) than human cases (19%) (p < 0.001). CONCLUSIONS: Isolates from all hosts clustered largely into previously identified genetic groups, with 3 haplotypes being shared between human and canine isolates confirming that B. dermatitidis isolates capable of infecting both species occur in nature. Allelic diversity measures trended higher in veterinary samples, with a higher number of total alleles and private alleles. Veterinary isolates of B. dermatitidis contributed a substantial amount of diversity to the overall population genetic structure demonstrating the importance of including veterinary isolates in genetic studies of evolution and virulence in this organism.